The Role of Text Structure in Encoding Ideology and Individual Perspective - María José Luzón Marco (Miscelánea: A Journal of English and American Studies)
Although any aspect of discourse can be ideologically significant, research on the relation between discourse and ideology has generally focused on the ideological investment of lexis and grammar. This paper analyses the ideological significance of the structure of the text. The role of text structure in perpetuating existing power relations is examined and described in terms of naturalisation and manipulation. Naturalisation of discourse structure refers to the fact that a structure associated with a specific social group is considered to be universal and thus the ideology which invests it is not regarded as ideology, but as common sense. Manipulation is concerned with the fact that, when encoding an argument, the writer considers the reader’s expectations regarding the structure of the text in order to articulate the different elements and organise the discourse in a specific way, which reflects the ideological position from which the text is constructed.